Compulsory Arbitration, Arbitral Risk and Negotiated Settlements: A Case Study in Bargaining under Imperfect Information - Crawford, Vincent P. (Review of Economic Studies, 1982)
The effect of conventional and final-offer compulsory arbitration on negotiated settlements is characterized, using Nash's variable-threats bargaining solution, with particular attention to the interaction between arbitral risk and bargainers' risk preferences. When there is no arbitral risk, both schemes are shown to have the same effect on negotiated settlements under very general conditions, even when bargaining is over several issues. Whether or not there is arbitral risk, negotiated settlements favour a bargainer more if his opponent is more risk-averse. On the other hand, increases in arbitral risk need not improve the position of the less risk-averse bargainer. As a by-product of the analysis, Kihlstrom, Roth and Schmeidler's risk-sensitivity results for the Nash and Raiffa-Kalai-Smorodinsky solutions are generalized from fixed-threats to variable-threats bargaining.